2016
DOI: 10.1097/gme.0000000000000625
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training reduces the frequency of menopausal hot flushes by improving thermoregulatory control

Abstract: Objectives: Post-menopausal hot flushes occur due to a reduction in oestrogen production causing thermoregulatory and vascular dysfunction. Exercise training enhances thermoregulatory control of sweating, skin and brain blood flow. We aimed to determine if improving thermoregulatory control and vascular function with exercise training alleviated hot flushes.Methods: Twenty one symptomatic females completed a 7-day hot flush questionnaire and underwent brachial artery flow-mediated dilation and a cardiorespirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 70 publications
2
34
0
Order By: Relevance
“…Furthermore, hormone dysregulation during the menopause transition is thought to lead to a narrowing of the thermoneutral zone, resulting in increased VMS severity and thereby increased episodes of insomnia. While exercise interventions may arguably widen the thermoneutral zone or increase the sensitivity to temperature changes during VMS [26], existing multi-center exercise interventions have failed to demonstrate improvements in VMS [27,28]. In the present study, women who reported higher exercise frequency had modestly less severe menopause-related symptoms.…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, hormone dysregulation during the menopause transition is thought to lead to a narrowing of the thermoneutral zone, resulting in increased VMS severity and thereby increased episodes of insomnia. While exercise interventions may arguably widen the thermoneutral zone or increase the sensitivity to temperature changes during VMS [26], existing multi-center exercise interventions have failed to demonstrate improvements in VMS [27,28]. In the present study, women who reported higher exercise frequency had modestly less severe menopause-related symptoms.…”
Section: Discussionmentioning
confidence: 59%
“…a protocol to examine thermoregulatory control rather than examine responses during hot flush) before and after an exercise training intervention (Bailey et al . ). We found that exercise training improves thermoregulatory control and enhances the function of the cerebral and cutaneous circulations to passive heating alongside improvements in the frequency of menopausal hot flushes (Bailey et al .…”
Section: Discussionmentioning
confidence: 97%
“…We found that exercise training improves thermoregulatory control and enhances the function of the cerebral and cutaneous circulations to passive heating alongside improvements in the frequency of menopausal hot flushes (Bailey et al . ). More specifically, exercise training mediated a reduction in resting core temperature that enabled an earlier onset of sweating and cutaneous vasodilatation, improved sensitivity of sweating and attenuated reductions in cerebral blood flow during passive heating.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations